ANNUAL GROWTH OF MOSSES IN MIDDLE-TAIGA PINE FORESTS WITH UNDERGROWTH IN THE REPUBLIC OF KARELIA - N. V. Genikova; A. Ju. Karpechko; R. P. Obabko; V. L. Mironov; S. A. Kutenkov (Вопросы лесной науки)
The article presents morphological characteristics for determining the annual growth of common species of green and sphagnum mosses growing in Karelia. The species studied include Pleurozium schreberi, Hylocomium splendens, mosses from the genus Dicranum, Aulacomium palustre, Ptilium crista-castrensis, Polytrichum commune, and mosses from the genus Sphagnum. The distinguishing features of annual growth were identified based on literature data and our own observations. To test the methodology, an analysis of the effects of different types of pine forests and the crown of pine on the annual growth values of Pleurozium schreberi, Hylocomium splendens, and Dicranum polysetum was conducted. It was found that Pleurozium schreberi contributes the most to the total annual production of the moss layer in the surveyed pine forests (41.4±6.3 g/m²). The average annual growth values for Hylocomium splendens and Dicranum polysetum were 5.9±1.1 and 4.8±1.1 g/m², respectively. In blueberry pine forests on sandy soils, the annual production of Pleurozium schreberi under pine canopies was twice as high compared to open spaces between canopies (61.2±11.8 and 29.9±9.3 g/m², respectively).